Helicobacter pylori infection may influence prevalence and disease course in myelin oligodendrocyte glycoprotein antibody associated disorder (MOGAD) similar to MS but not AQP4-IgG associated NMOSD - Malli, Chaithra; Pandit, Lekha; D’Cunha, Anita; Sudhir, Akshatha (Frontiers in Immunology, 2023)
Background: Helicobacter pylori (Hp) persists after colonizing the gut in childhood, and potentially regulates host immune system through this process. Earlier studies have shown that Hp infection in childhood, may protect against MS in later life. Such an association was not seen with AQP4-IgG positive NMOSD, while the association with MOGAD is unclear. Objective: To evaluate frequency of Hp IgG among patients with MOGAD, MS, NMOSD and matched controls and its effect on disease course. To ascertain whether childhood socio economic factors were linked to prevalence of Hp infection. Methods: In all, 99 patients diagnosed to have MOGAD, 99 AQP4 IgG+ NMOSD, 254MS and 243 matched controls were included. Patient demographics, diagnosis, age at disease onset, duration and the last recorded expanded disability status scale (EDSS) were obtained from our records. Socioeconomic and educational status was queried using a previously validated questionnaire. Serum HpIgG was detected using ELISA kits (Vircell, Spain). Result: Frequency of Hp IgG was significantly lower among MOGAD (28.3% vs 44%, p-0.007) and MS (21.2% vs 44%, p-0.0001) but not AQP4-IgG+ NMOSD patients (42.4% vs 44%, p-0.78) when compared to controls. Frequency of Hp IgG in MOGAD & MS patients combined (MOGAD-MS) was significantly lower than those with NMOSD (23.2% vs 42.4%, p- 0.0001). Seropositive patients with MOGAD- MS were older (p-0.001. OR -1.04, 95% CI- 1.01- 1.06) and had longer disease duration (p- 0.04, OR- 1.04, 95% CI- 1.002- 1.08) at time of testing. Educational status was lower among parents /caregivers of this study cohort (p- 0.001, OR -2.34, 95% CI- 1.48-3.69) who were Hp IgG+. Conclusions: In developing countries Hp infection may be a significant environmental factor related to autoimmune demyelinating CNS disease. Our preliminary data suggests that Hp may exert a differential influence - a largely protective role for MS-MOGAD but not NMOSD and may influence disease onset and course. This differential response maybe related to immuno-pathological similarities between MOGAD and MS in contrast to NMOSD. Our study further underscores the role of Hp as a surrogate marker for poor gut hygiene in childhood and its association with later onset of autoimmune diseases.